Enhanced Acid Orange 7 Adsorption by a Novel Organophosphorus-Modified Bentonite: Performance and Mechanistic Insights - Nouria Mahrez; Fatima Zohra Belkacem; Amine Amar; Mounir Khelifa; Ali Çoruh; Fatima Boucif; Fatiha Bessaha; Kheira Marouf-Khelifa; Amine Khelifa (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
Water contamination by Acid Orange 7 (AO7), a widely used anionic azo dye in the textile industry, represents a major environmental concern due to its persistence and potential to generate toxic aromatic amines. Herein, we report the synthesis of a novel organobentonite (BPA6) via intercalation of phenylphosphonic acid into bentonite, an organoclay previously unexplored for pollutant removal. XRD analysis revealed an expansion of the basal spacing from 10 to 15.4 Å with an intercalation rate of 86%, while FTIR and SEM confirmed structural reorganization and successful incorporation of phenylphosphonic functional groups. The modification increased interlayer accessibility and introduced additional P–OH active sites, enhancing hydrogen-bond donor density. Consequently, BPA6 achieved a maximum adsorption capacity of 123.3 mg.g⁻¹ at 55 °C, significantly exceeding raw bentonite. The kinetics were well described by the pseudo-second-order model, while the equilibrium data fit best with the Langmuir–Freundlich model. Thermodynamic analysis indicated a predominantly physisorption-driven process. BPA6 maintained stable performance over multiple regeneration cycles. Mechanistic insight was obtained by correlating spectroscopic, adsorption, and thermodynamic data, revealing a clear relationship between structure, surface chemistry, interactions, and performance. The adsorption mechanism is primarily governed by hydrogen bonding between Si–OH and intercalated P–OH moieties and the sulfonate and amine moieties of AO7. Phenylphosphonic acid intercalation optimizes clay surface chemistry, enhancing dye adsorption by BPA6 and highlighting its potential as a sustainable, high-performance wastewater adsorbent. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).